VD_FINDINFO HC / 2010 / 624 vom 16. September 2010 - VD Tribunal cantonal (2010)
MESURE PROVISIONNELLE, OBLIGATION D'ENTRETIEN, PENSION D'ASSISTANCE, PROCÉDURE | 176 CC, 444 al. 1 ch. 3 CPC, 465 al. 1 CPC